2020
DOI: 10.1371/journal.pone.0239761
|View full text |Cite
|
Sign up to set email alerts
|

Differences in length of stay and discharge destination among patients with substance use disorders: The effect of Substance Use Intervention Team (SUIT) consultation service

Abstract: Background Addiction medicine consultation services (ACS) may improve outcomes of hospitalized patients with substance use disorders (SUD). Our aim was to examine the difference in length of stay and the hazard ratio for a routine hospital discharge between SUD patients receiving and not receiving ACS. Methods Structured EHR data from 2018 of 1,900 adult patients with a SUD-related diagnostic code at an urban academic health center were examined among 35,541 total encounters. Cox proportional hazards regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
0
28
0
1
Order By: Relevance
“…To date, a few studies have evaluated various strategies to prevent irregular discharge, although they have primarily focused on patients with SUD. 30,32,33 For example, using retrospective data from over 35 000 hospital-related treatment encounters for SUD, Thompson et al found that compared with usual care, a substance use intervention team (SUIT) was associated with a significantly greater probability that patients would leave with a regular discharge (HR = 1.16, 95% CI 1.03–1.3). 32 The SUIT intervention focuses on harm reduction and includes interventions such as medication initiation, motivational interviewing, treatment education and processes to facilitate post-discharge care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, a few studies have evaluated various strategies to prevent irregular discharge, although they have primarily focused on patients with SUD. 30,32,33 For example, using retrospective data from over 35 000 hospital-related treatment encounters for SUD, Thompson et al found that compared with usual care, a substance use intervention team (SUIT) was associated with a significantly greater probability that patients would leave with a regular discharge (HR = 1.16, 95% CI 1.03–1.3). 32 The SUIT intervention focuses on harm reduction and includes interventions such as medication initiation, motivational interviewing, treatment education and processes to facilitate post-discharge care.…”
Section: Discussionmentioning
confidence: 99%
“…30,32,33 For example, using retrospective data from over 35 000 hospital-related treatment encounters for SUD, Thompson et al found that compared with usual care, a substance use intervention team (SUIT) was associated with a significantly greater probability that patients would leave with a regular discharge (HR = 1.16, 95% CI 1.03–1.3). 32 The SUIT intervention focuses on harm reduction and includes interventions such as medication initiation, motivational interviewing, treatment education and processes to facilitate post-discharge care. 32 In a study of veterans discharged from an in-patient mental health recovery and rehabilitation programme, Decker et al also found that small group, patient-centred therapy interventions were associated with significant improvements in successful treatment completion and better treatment retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rush launched a multidisciplinary Substance Use Intervention Team (SUIT) to address the opioid epidemic through a Screening, Brief Intervention, and Referral to Treatment (SBIRT) program with an inpatient Addiction Consult Service in October 2017. 22 , 23 Part of the SUIT initiative included the following single question universal drug screen: “How many times in the past year have you used an illegal drug or used a prescription medication for non-medical reasons?” (≥ 1 is positive). The single-question screen was administered by nursing staff as a part of the admission battery of questions to patients admitted to Rush’s 18 inpatient medical and surgical wards.…”
Section: Methodsmentioning
confidence: 99%
“…2 Given that people with OUD tend to have high utilization of emergency room and inpatient services, efforts at initiating treatment (eg, MOUD) and improving access to overdose-reversing medications (eg, naloxone) via acute care initiatives are increasing. [4][5][6] In the outpatient setting, pharmacists have made many efforts to collaborate with waivered prescribers to increase OUD treatment access and prescribing. [6][7][8] These collaborative models have demonstrated similar levels of care for MOUD management, improved adherence and retention to MOUD, and extended the care of waivered physicians.…”
mentioning
confidence: 99%